2022
DOI: 10.3389/fpls.2022.951752
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements and Development in Nano-Enabled Agriculture for Improving Abiotic Stress Tolerance in Plants

Abstract: Abiotic stresses, such as heavy metals (HMs), drought, salinity and water logging, are the foremost limiting factors that adversely affect the plant growth and crop productivity worldwide. The plants respond to such stresses by activating a series of intricate mechanisms that subsequently alter the morpho-physiological and biochemical processes. Over the past few decades, abiotic stresses in plants have been managed through marker-assisted breeding, conventional breeding, and genetic engineering approaches. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 135 publications
0
9
0
Order By: Relevance
“…Abiotic pressures such as salinity and drought are spurred on by unpredictable shifts in the climate, which eventually reduce agricultural output and damage natural resources (Shahzad et al, 2018 ). The bulk of these abiotic stress events, that vegetation experiences at different stages of their life cycle, cause crops to establish a variety of defensive responses, which can have the unintended and harmful effect of altering their physiological functions (Manzoor et al, 2022 ). Organic agriculture has been utilized for decades as an ecologically sound way to boost crop yields while protecting the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic pressures such as salinity and drought are spurred on by unpredictable shifts in the climate, which eventually reduce agricultural output and damage natural resources (Shahzad et al, 2018 ). The bulk of these abiotic stress events, that vegetation experiences at different stages of their life cycle, cause crops to establish a variety of defensive responses, which can have the unintended and harmful effect of altering their physiological functions (Manzoor et al, 2022 ). Organic agriculture has been utilized for decades as an ecologically sound way to boost crop yields while protecting the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that the detrimental effects of high HM concentrations on crops are due to the impairment of bio-macromolecules, disruption of ion balance, excessive reactive oxygen species (ROS) generation and toxic radicals/induction of oxidative stress, and damage to photosynthetic apparatus. Various approaches, e.g., marker-mediated breeding, transgenic crop engineering, and conventional breeding, have been created to lower the effects of HMs on crops [ 3 , 4 ]. On the other hand, in recent years, nano-based techniques have emerged as highly promising approaches to regulating abiotic stresses induced by the environment, enhancing agricultural productivity, addressing nutrient deficiencies, and revolutionizing biological systems [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soil Security, Vol. 7 (2023) tolerance to abiotic and biotic stresses using nanoenabled agro-materials (Manzoor et al 2022), entranced accumulation of nano-agro-chemicals in plants , investigations into the nanotoxicology of nano-enabled materials (White et al 2022), impacts of nano-enabled agrochemicals on soil microbial communities (Ahmed et al 2023), and seed treatment using nanomaterials for sustainable agriculture (Shelar et al 2023). These nanoagrochemicals include organic (e.g., carbon nano dots; Liu et al 2020) and inorganic (e.g., metallic/ metalloids like nano-selenium; Samynathan et al 2023) sources that can support crop productivity.…”
Section: Introductionmentioning
confidence: 99%